Plus-sized misadventures in love! 3 - Mamakari (HarperAlley, an imprint of HarperCollins Publishers, 2026)
Yumeko and the vice president grow closer, but the rumors of his forbidden love look increasingly true. So, Yumeko dedicates herself to being the best friend the vice president could ever want. But will it ever be more than that for her?